Towards an Integrated Approach to Improve the Understanding of the Relationships Between Water-Borne Infections and Health Outcomes: Using Malaysia as a Detailed Case Study - Ho, Jia Yee; Lavinya, Amanda Anne; Kay, Dominic Shuen Wei; Lee, Cindy Ik Sing; Razmi, Ahmad Haikal; Walsh, Claire L.; Goodson, Michaela L.; Eswaran, Jeyanthy (Frontiers in Water, 2022)
As in many low- and middle-income countries around the world, thousands of local communities in Southeast Asia rely on river water to sustain their livelihoods. However, poor water quality threatens the health of both humans and ecosystems. The aim of this review was to examine the available literature to investigate how health outcomes in Malaysia have been studied and reported as directly attributable to human infections from river water. Computer-aided searches from ten electronic databases were undertaken, with searches limited to the English language and publication dates since January 2010. The literature search revealed that the predominant river water infections identified in Malaysia were bacterial (coliforms, Salmonella spp., typhoid, leptospirosis, melioidosis), viral (including dengue, hepatitis, enterovirus), parasitic infections including amoebiasis, giardiasis and cryptosporidiosis, helminth infections, Blastocystis infections and sarcocystosis. No studies were found that have attempted to evaluate the impact of water related infection on human health longitudinally. Moreover, the possibility of integrated water governance systems that could reduce infection and improve water quality, particularly for marginalised groups have not been discussed or studied. Several cross-sectional studies identified infections at a point in time, but large longitudinal data sets of water infection parameters and how they influence human health outcomes have not been reported. Using Malaysia as a demonstration case study, we suggest a number of recommendations based on using a systems approach to tackle the challenges involved in data collection and integration, which is central to the understanding, strategic planning and management of water-borne infections.